The Factors Influencing the Use of Address terms in English and Gorontalese: A Sociolinguistic Analysis - Hamzah, Aryati (The Eastasouth Journal of Learning and Educations, 2024)
Communication plays a vital role in human interaction, enabling the exchange of ideas, feelings, and thoughts. In conversation, address terms reflect linguistic and social dynamics, signifying relationships, social status, and cultural norms. This study contrasts the use of address terms in English and Gorontalese within sociolinguistic contexts, focusing on factors influencing their application: situational context, marital status, and emotional expression. A descriptive qualitative method with contrastive analysis was employed, drawing data from literature, Gorontalo linguistic sources, and English interactions. Findings reveal that in formal settings, Gorontalese speakers utilize titles and Indonesian language for respect, while English speakers rely on terms such as "Mr.," "Mrs.," and combinations with job titles. Non-formal contexts in Gorontalo involve kinship terms like "Baba" and "Mama," whereas English uses pet names or nicknames. Marital status influences address terms, with Gorontalese speakers assigning specific nicknames for married individuals, while English speakers use titles like "Mrs." Emotional factors also affect usage; in Gorontalo, affectionate terms with varying intonations convey emotions, including anger, contrasting with English’s consistent address terms. The study underscores the importance of address terms as cultural markers, highlighting their roles in fostering social harmony and mutual respect in communication. These findings contribute to a deeper understanding of the sociolinguistic diversity between English and Gorontalese.